2005
DOI: 10.1111/j.1365-2621.2005.tb09068.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antimutagenic Activity of Phenolic Compounds in Newly Harvested and Stored Common Beans Phaseolus vulgaris against Aflatoxin B1

Abstract: : Phenolic compounds were extracted from recently harvested or stored black Jamapa beans (Phaseolus vulgaris) that were subjected or not to thermal treatment. The beans studied were cropped in the same area and were from the same lot. The highest amount of condensed tannins (CT) was found in the seed coat of recently harvested beans [222.41 ± 16mg of (+)‐catechin equivalents per gram of seed coat]. After 2 yof storage, the amount of CT dropped significantly [35.8 ± 3.4 mg of (+) ‐catechin equivalents per gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 36 publications
6
56
0
5
Order By: Relevance
“…Colored common beans have high relative abundances of anthocyanins. These compounds have been reported elsewhere for common beans [22]. Rutin (0.51-8.51%), quercetin (0.52-4.48%), and kaempferol-3-O-glucoside (0.48-72.63%) were identified in ten, seven, and twelve common beans, respectively.…”
Section: Polyphenol Compounds In Common Beansmentioning
confidence: 87%
“…Colored common beans have high relative abundances of anthocyanins. These compounds have been reported elsewhere for common beans [22]. Rutin (0.51-8.51%), quercetin (0.52-4.48%), and kaempferol-3-O-glucoside (0.48-72.63%) were identified in ten, seven, and twelve common beans, respectively.…”
Section: Polyphenol Compounds In Common Beansmentioning
confidence: 87%
“…In our study, even though beans contain high levels of protein, the ADC I was low in juveniles and adults. Aparicio-Fernández et al (2005) reported that beans contained 4.1 mg g -1 of tannins after thermal processing. The adverse effect of tannic acid on tilapia was studied by Al-Owafeir (1999), who found a significant reduction in the growth of tilapia that were fed diets containing as low as 0.27% tannic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Beans were cooked using a ''traditional'' cooking process according to the method of Aparicio-Fernandez et al (2005). The AOAC method 991.43 (AOAC 2002) was used to obtain total dietary fiber (TDF) considered here as the NDF.…”
Section: Non-digestible Fraction Extractionmentioning
confidence: 99%